2010
DOI: 10.1016/j.jvs.2009.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of low-strength compression stockings with bandages for the treatment of recalcitrant venous ulcers

Abstract: Our study illustrates the difficulty of bringing large and long-standing venous ulcers to heal. The effect of compression with MCS was not different from that of compression with bandages. Both treatments alleviated pain promptly. Quality of life was improved only in patients whose ulcers had healed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 16 publications
0
50
0
5
Order By: Relevance
“…23,27 Numerous studies have proven the effect of compression therapy on venous and lymphatic system, 1,19,31 whether compression is performed with bandages or stockings. 5 The efficacy of the treatment mainly depends on the level of pressure which is applied on the limb. 14,24 This level of pressure depends on several parameters such as: -Other parameters such as friction between the different layers, mechanical properties of the limb soft tissues,……”
Section: Introductionmentioning
confidence: 99%
“…23,27 Numerous studies have proven the effect of compression therapy on venous and lymphatic system, 1,19,31 whether compression is performed with bandages or stockings. 5 The efficacy of the treatment mainly depends on the level of pressure which is applied on the limb. 14,24 This level of pressure depends on several parameters such as: -Other parameters such as friction between the different layers, mechanical properties of the limb soft tissues,……”
Section: Introductionmentioning
confidence: 99%
“…Healing within 90 days was observed in 36% of patients using MCS and in 48% using four layers compression bandages (P = 0.35). Healing within 180 days was documented in 50% of MCS patients and in 67% with four layers compression bandages (P = 0.21) [12].…”
Section: Discussionmentioning
confidence: 97%
“…It is important to emphasize that the patients belonged to the group of refractory cases included in the previous study already mentioned. 16 This assay showed that 50% of ulcers showed complete closure using medical compression stockings, and 67% of complete closure with multilayer bandages, after 180 days.…”
Section: Discussionmentioning
confidence: 99%
“…Nine patients were selected from a cohort of 55 patients who had previously completed the aforementioned comparative study of lowstrength medical compression stockings with bandages for treating recalcitrant venous ulcers, 16 after a long period without showing any improvement in the ulcers' features (e.g. dimensions, color intensity of dyschromia), as well as pain and CIVIQ.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation